2022
DOI: 10.3390/ijms23073775
|View full text |Cite
|
Sign up to set email alerts
|

In Pancreatic Adenocarcinoma Alpha-Synuclein Increases and Marks Peri-Neural Infiltration

Abstract: α-Synuclein (α-syn) is a protein involved in neuronal degeneration. However, the family of synucleins has recently been demonstrated to be involved in the mechanisms of oncogenesis by selectively accelerating cellular processes leading to cancer. Pancreatic ductal adenocarcinoma (PDAC) is one of the most lethal human cancers, with a specifically high neurotropism. The molecular bases of this biological behavior are currently poorly understood. Here, α-synuclein was analyzed concerning the protein expression in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 72 publications
1
7
0
Order By: Relevance
“…An increased expression of αS in melanoma compared to normal tissue (Figure 2B) correlates perfectly with previous reports [59,69]. This is also the case for pancreatic adenocarcinoma, where an incremental expression was recently described [70]. However, there is a significant decrease in expression for this member of the family in colon adenocarcinoma in contrast with the increased protein level reported in colorectal cancer [57].…”
Section: Synucleins Are Cancer-related Proteinssupporting
confidence: 91%
“…An increased expression of αS in melanoma compared to normal tissue (Figure 2B) correlates perfectly with previous reports [59,69]. This is also the case for pancreatic adenocarcinoma, where an incremental expression was recently described [70]. However, there is a significant decrease in expression for this member of the family in colon adenocarcinoma in contrast with the increased protein level reported in colorectal cancer [57].…”
Section: Synucleins Are Cancer-related Proteinssupporting
confidence: 91%
“…α-synuclein is not expressed in grade 1 meningioma but expressed in grade 2 and 3 meningiomas, consistent with a role of α-synuclein in disease progression [3]. In pancreatic cancer, α-synuclein expression was correlated to neurotropism, a sign of tumor progression [4]. Evidence of the β-synuclein in cancer is scarce, although its expression is seen in brain tumors including ependymoma, astrocytoma, oligodendroglioma, and medulloblastoma [5].…”
Section: Fulltextmentioning
confidence: 77%
“…A diagnosis of T-ALL was made. Cytogenetic analysis of bone marrow showed a complex karyotype 45,XX,t(5;12)(q35;p13),t(7;9)(q34;q22),add(12)(p13),der(13)del(13)(q14q32)t(12;13) (p13;q34),-21[16]/46,XX [4] (Fig. 1B).…”
Section: Fulltextmentioning
confidence: 99%
“…In a meta-analysis of genetic parkinsonism and cancer, SNCA was predominantly associated with gastrointestinal cancers [ 70 ], such as colorectal cancer [ 71 ]. Matteo Bianchini and co-workers discovered that α-syn was significantly upregulated in PDAC [ 72 ]. Nevertheless, our study found that SNCA was positively associated with the survival rate of PAAD patients, suggesting that an intricate molecular mechanism exists between SNCA and PAAD that needs to be further explored.…”
Section: Discussionmentioning
confidence: 99%